Urogynäkologische Aus- und Weiterbildungssituation in Deutschland: Kluft zwischen Anspruch und Realität = Urogynaecological training situation in Germany : Gap between demand and reality - Kranz, Jennifer; Schott, Sarah; Pelzer, Alexandre E. (Der Urologe, 2016)
BackgroundWith increasing life expectancy, progressive demographic change and decreasing societal stigmatization of incontinence urologists and gynaecologists are increasingly faced with urogynaecological challenges. To date however, urogynaecology is a poorly standardized area of expertise in both disciplines. Therefore, the urogynaecology training, especially in Germany, is very heterogeneous and requires evaluation as well as improvement.Materials and methodsThe GeSRU-Academics research group “Functional urology and LUTS” evaluated this subject nationwide among urological and gynecological trainees and their chief physicians by using a comprehensive questionnaire (34/38 multiple-choice items) between April 2015 and May 2016.Results336 urological residents and 190 chief physicians as well as 171 gynaecological residents and 175 chief physicians participated in the survey. Of all trainees, 70.0 % stated a personal interest in urogynaecology, but 45.4 % (gynaecological residents) and 52.9 % (urological residents) mention not to receive a standardized training in their own department. The chief physicians’ survey resulted in discrepancies concerning the same question, <10 % of all residents do not receive a standardized urogynaecological training from their point of view. However, standardized urogynaecological training is of importance for those chief physicians.ConclusionsThere is a discrepancy between expectations and reality of urogynaecological education and training. To enable a well-structured and standardized urogynaecological education and training, it is compulsory to focus on an interdisciplinary cooperation and to promote multidisciplinary development. A broad-based, well-designed training network and curricula should be established and used consistently.